Tobacco Control Policies and Sociodemographic Disparities in Cigarette Smoking Behaviors in the U.S.: A Systematic Review Protocol - Catherine A. Vander Woude, MPH; James H. Buszkiewicz, PhD; Nargiz Travis, MScPH; LaTeesa N. James, MLIS; Nancy L. Fleischer, PhD (Elsevier, 2024)
Since the 1998 Master Settlement Agreement in the U.S., many studies have examined the associations between tobacco control policies and smoking; however, there is a need to comprehensively examine the impact of these policies on sociodemographic disparities in cigarette smoking. This protocol outlines a systematic review that seeks to fill this gap. Quantitative observational, experimental, and quasi-experimental studies are eligible for inclusion. Policies include cigarette taxes, smoke-free air laws, anti-tobacco media campaigns, and Tobacco 21 laws implemented in the U.S. Outcomes include cigarette smoking initiation, prevalence, and cessation among youth and adults. Sources to be searched include Clarivate BIOSIS, EBSCO CINAHL Plus, Cochrane Library, Ovid MEDLINE, PsycINFO, Sociological Abstracts, Clarivate Web of Science Core Collection, and the National Bureau of Economic Research. Included studies must be written in English. Two independent reviewers will screen and analyze relevant articles and then extract data on participants, context, methods, and key findings. Studies will be assessed using the Joanna Briggs Institute critical appraisal checklists and presented in 2 reviews: 1 youth focused (aged <18 years) and 1 adult focused (aged ≥18 years). The findings are intended to inform the creation of new and potentially more targeted tobacco control policies to improve health equity.